Chinese Medicine Treatment for Afatinib-Induced Paronychia - Pei-Yuu Yang; Chen-Jei Tai (Case Reports in Oncological Medicine)
Afatinib (Gilotrif™) is widely used to treat patients with mutant activating epidermal growth factor receptor- (EGFR-) dependent lung adenocarcinoma; however, it has various adverse side effects. Here, we report a patient with afatinib-induced paronychia. After Chinese medicine treatment with the well-known anticancer Chinese herbs, Jen-Ren-Hwo-Minq-Saan, and decoction of Ban-Zhi-Lian (Scutellaria barbata) with Bai-Hua-She-She-Cao (Hedyotis diffusa Willd), patient’s condition was significantly improved. This shows that these Chinese medicines can not only be used in cancer treatment but also be used in the afatinib-induced paronychia.